PHYTOCHEMICAL SCREENING, GAS CHROMATOGRAPHY–MASS SPECTROMETRY PROFILING, IN VITRO CYTOTOXICITY, AND ANTHELMINTIC ACTIVITY OF HYDROALCOHOLIC EXTRACT OF DURANTA ERECTA LEAVES - R, RAJESWARI; PRABHAKARAN V; SARAVANAKUMAR A (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study aims at the preliminary phytochemical evaluation, gas chromatography–mass spectrometry (GC–MS) analysis, in vitro cytotoxicity, and anthelmintic activity of the hydroalcoholic extract of D. erecta leaves. Methods: The hydroalcoholic extraction of the plant material is done with Soxhlet apparatus and the GC–MS profiling of the extract is performed. The in vitro cytotoxicity activity of the extract is done using the MOLT-3 cell lines. The anthelmintic activity is performed using Pheretima posthuma. Results: The GC–MS analysis shows the presence of various secondary metabolites with proved pharmacological activity. The in vitro cytotoxicity and the anthelmintic activity of the extract show the beneficial effect of the plant. Conclusion: The flavonoids, phenolic compounds, and tannins present in the plant extract may support the cytotoxic and anthelmintic activity of the plant.